2017
DOI: 10.1186/s13613-017-0280-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a multifaceted intervention including sepsis electronic alert system and sepsis response team on the outcomes of patients with sepsis and septic shock

Abstract: BackgroundCompliance with the clinical practice guidelines of sepsis management has been low. The objective of our study was to describe the results of implementing a multifaceted intervention including an electronic alert (e-alert) with a sepsis response team (SRT) on the outcome of patients with sepsis and septic shock presenting to the emergency department.MethodsThis was a pre–post two-phased implementation study that consisted of a pre-intervention phase (January 01, 2011–September 24, 2012), intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 48 publications
0
55
1
8
Order By: Relevance
“…Although no studies have reported implementing these types of interventions to reduce opioid prescribing for patients with cancer, both Enablement and Environmental restructuring interventions have been used to improve compliance with evidence-based guidelines for managing sepsis. 40,41 These interventions are particularly well-suited for surgical patients with cancer. For example, patients with cancer report high levels of psychological distress, 10,11 and surgeons in our study reported difficulty adequately counseling patients on safe opioid use because patients are distracted by coping with a new cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although no studies have reported implementing these types of interventions to reduce opioid prescribing for patients with cancer, both Enablement and Environmental restructuring interventions have been used to improve compliance with evidence-based guidelines for managing sepsis. 40,41 These interventions are particularly well-suited for surgical patients with cancer. For example, patients with cancer report high levels of psychological distress, 10,11 and surgeons in our study reported difficulty adequately counseling patients on safe opioid use because patients are distracted by coping with a new cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 The use of early warning scores has been shown to predict in-hospital mortality and, when paired with a trigger to a provider, can lead to improved sepsis care. 12 , 14 Given the significant costs associated with sepsis patients, we assessed the clinical and financial impact of implementing an EHR-based, modified Early Warning Score (mEWS) alerting system for decompensating septic patients in an academic medical center (Appendix Figure 1 and Section 2). We hypothesized that earlier recognition of new sepsis or decompensating septic patients on the floor may improve clinical and financial outcomes.…”
Section: Background and Significancementioning
confidence: 99%
“…Clinical decision support (CDS) systems may play a role in improving bundle compliance and delivery of timely treatment. CDS sepsis early warning systems leverage electronic health information to continuously stratify patients for the risk of sepsis and alert clinicians [ 17 - 22 ]. Unfortunately, many sepsis CDS systems fail to improve outcomes because of poor diagnostic accuracy and program implementation [ 23 - 25 ].…”
Section: Introductionmentioning
confidence: 99%